2019
DOI: 10.1016/j.snb.2019.05.023
|View full text |Cite
|
Sign up to set email alerts
|

A wireless smart patch for the controlled repetitive transdermal administration of therapeutic agents

Abstract: A thermoresistive transdermal drug delivery patch based on a n-alkane wax phase change film is described. A composite structure comprising a screen printed silver chloride heater sandwiched with a wax film loaded with diclofenac was developed and the release characteristics upon heating were investigated. The drug is shown to be immobile within the solid film (off state) but is readily delivered upon heating beyond the transition temperature (37 °C). Drug delivery is maintained while the heater is active and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Although it has been reported that thermal stimulation is harmless for epidermal drug delivery, [32] increasing the temperature of the skin to more than 45 °C range could be potentially damaging to the skin. [33][34][35] Therefore, to minimize any type of damage to the skin surface, the paper-based delivery platform was printed on a thick filter paper substrate (180 µm thickness) to minimize any potential heat transfer to the skin by the printed heater.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been reported that thermal stimulation is harmless for epidermal drug delivery, [32] increasing the temperature of the skin to more than 45 °C range could be potentially damaging to the skin. [33][34][35] Therefore, to minimize any type of damage to the skin surface, the paper-based delivery platform was printed on a thick filter paper substrate (180 µm thickness) to minimize any potential heat transfer to the skin by the printed heater.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative option is to convert the drug to the polar form prior to encapsulation within the wax. This could be readily achieved if an appropriate salt formulation of the drug is available (i.e., diclofenac sodium salt [ 15 ]). Unfortunately, there are no commercial salt variants of curcumin.…”
Section: Resultsmentioning
confidence: 99%
“…Transdermal patches and microdevices that responsively alter a drug’s release dynamics upon being activated by mechanical, thermal, light, or electrical activation have begun to emerge in recent years [ 13 , 14 , 15 , 16 ]. In this particular case, the electrothermal activation of a phase-change material (PCM) was explored as a means of enabling the real-time modification of dosage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimuli‐responsive drug delivery systems potentially enable the treatment of such conditions because they have potential for spatiotemporally controlled drug delivery 8 . Indeed, materials responding to stimuli (such as enzymes, light, pH, temperature, ultrasound and electric/magnetic fields) have been developed for use as drug delivery devices, 9–24 with reviews specifically on the application of electroactive materials for drug delivery 25–31 …”
Section: Introductionmentioning
confidence: 99%